A Rare Case of Petrified Ear. (15th October 2012) - Buikema, Kathryn E.; Adams, Erin G.
Abstract : Calcification or ossification of the auricle, also referred to as petrified ear, is a rare diagnosis in dermatology. In medical literature, it has most often been attributed to trauma, hypothermia and frostbite, or hypercalcemia secondary to a metabolic or endocrine disorder, such as Addison's disease. Here, we report the clinical and radiologic findings of a 79-year-old African American male whose unilateral petrified auricle was an incidental finding. He had a preceding history of hyperparathyroidism and subsequent hypercalcemia treated with a subtotal parathyroidectomy three years prior to presentation. In addition to laboratory analysis, a history and physical examination was performed which revealed no other signs of hypercalcemia. Radiologic studies demonstrated partial ossification of the external auricular cartilage on the left side. The patient was diagnosed with the rare occurrence of a petrified ear. In light of this case, we provide a discussion concerning the possible etiologies of this diagnosis including appropriate patient evaluation and possible treatment recommendations.